Development of the Animated Video ‘Petualangan si Dara: Sel darah merah’ For Sixth-Grade Elementary School - Ummi Akhirul Hizami; Dyoty Auliya Vilda Ghasya; Nany Safrianty (Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas PGRI Yogyakarta, 2026)
The animated video media used by teachers in the complex IPAS subject still do not take into account student characteristics, even though these are key variables in the selection of instructional media. This study aims to develop animated video instructional media on the topic of the human circulatory system for the IPAS subject for sixth-grade students at Elementary School 14. This study is a research and development (R&D) study using the ADDIE model, though it is limited to the product testing phase. The results indicate that the product’s feasibility score for the content aspect is 0.91, meeting the “highly valid” criterion; 0.85 by language experts, also meeting the “highly valid” criterion; and a score of 0.96 for the design aspect, meeting the “highly valid” criterion. The teacher response test yielded a score of 3.7, meeting the “highly acceptable” criterion, followed by the student response test, which showed a positive response with a result of 86.1%, meeting the ‘excellent’ criterion. Based on the results of the product pilot test, the animated video learning resource “Petualangan si Dara: Sel darah merah,” covering the human circulatory system in the sixth-grade elementary school science curriculum, is suitable for use as a classroom learning resource.